Angiotensin II and the Cardiac Parasympathetic Nervous System in Hypertension - Julia Shanks (MDPI AG, 2021)
The renin–angiotensin–aldosterone system (RAAS) impacts cardiovascular homeostasis via direct actions on peripheral blood vessels and via modulation of the autonomic nervous system. To date, research has primarily focused on the actions of the RAAS on the sympathetic nervous system. Here, we review the critical role of the RAAS on parasympathetic nerve function during normal physiology and its role in cardiovascular disease, focusing on hypertension. Angiotensin (Ang) II receptors are present throughout the parasympathetic nerves and can modulate vagal activity via actions at the level of the nerve endings as well as via the circumventricular organs and as a neuromodulator acting within brain regions. There is tonic inhibition of cardiac vagal tone by endogenous Ang II. We review the actions of Ang II via peripheral nerve endings as well as via central actions on brain regions. We review the evidence that Ang II modulates arterial baroreflex function and examine the pathways via which Ang II can modulate baroreflex control of cardiac vagal drive. Although there is evidence that Ang II can modulate parasympathetic activity and has the potential to contribute to impaired baseline levels and impaired baroreflex control during hypertension, the exact central regions where Ang II acts need further investigation. The beneficial actions of angiotensin receptor blockers in hypertension may be mediated in part via actions on the parasympathetic nervous system. We highlight important unknown questions about the interaction between the RAAS and the parasympathetic nervous system and conclude that this remains an important area where future research is needed.